A separator for an electrochemical device

KR103032032B1Active Publication Date: 2026-10-13LG ENERGY SOLUTION LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
KR1020240032017
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-03-07
Filing Date
2024-03-06
Publication Date
2026-10-13
Estimated Expiration
2044-03-06
Patent Text Reader

Abstract

The present invention relates to a separator and an electrochemical device including the same. The separator of the present invention comprises a porous polyolefin substrate with improved wetting properties and a porous coating layer having excellent adhesion to the same. Specifically, the separator comprises a porous polyolefin substrate and a porous coating layer formed on at least one surface of the porous polyolefin substrate. The porous polyolefin substrate comprises a cross-linked polyolefin resin, and the cross-linked polyolefin resin comprises silicon-containing organic groups grafted to polyolefin chains. The porous coating layer comprises inorganic particles and a binder polymer, wherein the inorganic particles comprise boehmite (AlO(OH)).
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a separator for an electrochemical device and an electrochemical device including the same. Background Technology

[0002] Rechargeable batteries, typified by lithium-ion batteries, are widely used as power sources for portable electronic devices such as laptops, mobile phones, digital cameras, and camcorders. Furthermore, due to their high energy density, these batteries are recently being applied in various fields, including automobiles.

[0003] Lithium-ion batteries are gaining attention for their advantages, such as higher operating voltage and significantly greater energy density compared to conventional batteries using aqueous electrolytes, such as Ni-MH, Ni-Cd, and lead-acid batteries. However, these lithium-ion batteries have drawbacks, including safety issues like ignition and explosion associated with the use of organic electrolytes, as well as complex manufacturing processes. Recent lithium-ion polymer batteries are considered a next-generation battery due to improvements over these weaknesses; however, their capacity is still relatively lower compared to lithium-ion batteries, and their discharge capacity, particularly at low temperatures, is insufficient, making urgent improvements necessary.

[0004] It is very important to evaluate the stability of such electrochemical devices and ensure their safety. Regarding the safety characteristics of electrochemical devices, there is a high risk of explosion if the device overheats, causing thermal runaway, or if the separator is penetrated. In particular, polyolefin-based separator substrates, which are commonly used as separators for electrochemical devices, exhibit extreme thermal shrinkage behavior at temperatures above 100°C due to material properties and manufacturing process characteristics including stretching, which causes a short circuit between the anode and cathode.

[0005] In order to solve the safety issues of such electrochemical devices, a separator has been proposed in which a porous inorganic coating layer is formed by coating a mixture of an excess amount of inorganic particles and a binder polymer on at least one surface of a separator substrate having a large number of pores, and there is a continuing demand for further safety enhancement. For example, the need to strengthen the adhesion at the interface between the porous inorganic coating layer containing an excess amount of inorganic particles and the separator substrate is being discussed. The problem to be solved

[0006] Therefore, the problem that the present invention aims to solve is,

[0007] The present invention provides a separation membrane that enhances the wetting properties of the separation membrane substrate and improves the adhesion between the separation membrane substrate and a porous inorganic coating layer containing an excess amount of inorganic particles.

[0008] Thus, the present invention aims to provide an electrochemical device with improved stability and excellent resistance characteristics. means of solving the problem

[0009] In order to solve the above problem,

[0010] According to one aspect of the present invention, a separator substrate of the following embodiments is provided.

[0011] The separator substrate according to the first embodiment is,

[0012] It comprises a porous polyolefin substrate and a porous coating layer formed on at least one surface of the porous polyolefin substrate,

[0013] The above porous polyolefin substrate is,

[0014] It includes a cross-linked polyolefin resin,

[0015] The above-mentioned cross-linked polyolefin resin comprises silicon-containing organic groups grafted onto polyolefin chains, and

[0016] The above porous coating layer is,

[0017] It includes inorganic particles and binder polymers,

[0018] The above inorganic particles are said to contain boehmite (AlO(OH)).

[0019] According to the second embodiment, in the first embodiment,

[0020] The above porous polyolefin substrate is,

[0021] The gel fraction is 3% to 80%, and

[0022] The standard deviation (△d) of the thickness measured at at least 100 arbitrary points may be 0.5 μm or less.

[0023] According to the third embodiment, in the first embodiment or the second embodiment,

[0024] The adhesive strength between the porous polyolefin substrate and the porous coating layer may be 50 gf or more.

[0025] According to the fourth embodiment, in any one of the first to third embodiments,

[0026] The adhesion strength between the porous polyolefin substrate and the porous coating layer may be 70 to 95 gf.

[0027] According to the fifth embodiment, in any one of the first to fourth embodiments,

[0028] The content of the above boehmite is,

[0029] It may be 80% by weight or more based on the total weight of the above inorganic particles.

[0030] According to the 6th embodiment, in the 5th embodiment,

[0031] The above silicon-containing organic group is a residue derived from a vinyl group-containing silane compound, and

[0032] The above vinyl group-containing silane compound may include vinyltrimethoxysilane, vinyltriethoxysilane, vinyltriacetoxysilane, (3-methacryloxypropyl)trimethoxysilane, (3-methacryloxypropyl)triethoxysilane, vinylmethyldimethoxysilane, vinyl-tris(2-methoxyethoxy)silane, vinylmethyldiethoxysilane, or a mixture of two or more of these.

[0033] According to the seventh embodiment, in any one of the first to sixth embodiments,

[0034] The above porous polyolefin substrate may further include chromium (Cr).

[0035] According to the eighth embodiment, in any one of the first to seventh embodiments,

[0036] The chromium content may be 0.1 to 20 ppm.

[0037] According to the ninth embodiment, in any one of the first to eighth embodiments,

[0038] The crosslinked structure within the above-mentioned crosslinked polyolefin resin may include a structure derived from the result of a radical polymerization reaction between vinyl groups mediated by a thermal initiator.

[0039] According to the 10th embodiment, in any one of the 1st to 9th embodiments,

[0040] The above-mentioned thermal initiator may include a peroxide-based compound, a persulfate-based compound, an azo-based compound, or a mixture thereof.

[0041] According to another aspect of the present invention, electrochemical elements of the following embodiments are provided.

[0042] The electrochemical device according to the 11th embodiment is,

[0043] The structure includes an anode, a cathode, and a separator interposed between the anode and the cathode, wherein the separator is in accordance with one embodiment of the first to tenth embodiments. Effects of the invention

[0044] A separator according to one embodiment of the present invention can exhibit excellent adhesion between a porous polyolefin substrate and a porous coating layer, and excellent wetting properties of the separator substrate.

[0045] In particular, the porous polyolefin substrate used as the separator substrate may have improved thickness uniformity and heat resistance by including a large amount of cross-linked structures within the polyolefin chain, and may also have improved wettability with the electrolyte and improved adhesion between porous coating layers by including silicon-containing organic groups grafted onto the polyolefin chain. Additionally, the porous coating layer may have improved adhesion to the porous polyolefin substrate by including boehmite as an inorganic particle.

[0046] Thus, the effect of significantly improving operational stability, such as heat resistance characteristics, of an electrochemical device including a separator using such a separator substrate can be achieved, but the mechanism of the present invention is not limited thereto. Specific details for implementing the invention

[0047] The present invention will be described in detail below.

[0048] The present invention relates to a separator for an electrochemical device and an electrochemical device including the same. In the present invention, the electrochemical device is a device that converts chemical energy into electrical energy through an electrochemical reaction, and is a concept that includes primary batteries and secondary batteries. The secondary battery is capable of charging and discharging and is a concept that encompasses lithium-ion batteries, nickel-cadmium batteries, nickel-hydrogen batteries, etc.

[0049] In one embodiment of the present invention, the separator for the electrochemical device may be a Safety Reinforced Separator (SRS), a Ceramic Coated Separator (CCS), or a separator formed through other known manufacturing methods.

[0050] In one embodiment of the present invention, the SRS is receiving attention as a technology capable of improving adhesion between a membrane substrate and a porous coating layer because, in the manufacturing method, a solution-type binder resin, i.e., a binder resin-containing solution, is generally used when forming the porous coating layer, allowing the solution-type binder resin to permeate toward the porous membrane substrate. However, there is still a need for improvement, such as the problem of weak bonding strength with the solution-type binder resin due to the hydrophobic properties of the conventional membrane substrate, or the problem of inferior inherent adhesion of the porous coating layer due to a large amount of inorganic particles constituting the porous coating layer.

[0051] In another embodiment of the present invention, it is known that the CCS has a fundamentally inferior adhesion between the separator substrate and the porous coating layer compared to SRS because the absolute amount of binder resin used in the manufacturing method is generally smaller than that of the SRS manufacturing method, and a particulate binder resin is used when forming the porous coating layer.

[0052] According to one aspect of the present invention, the invention aims to provide a separation membrane with excellent adhesion between a separation membrane substrate and a porous coating layer, without being limited to a manufacturing method such as an SRS manufacturing method, a CCS manufacturing method, or other known manufacturing methods.

[0053] To this end, a separator for an electrochemical device according to one aspect of the present invention utilizes a separator substrate with improved heat resistance and wetting properties as described below, and has a porous coating layer with excellent adhesion to the separator substrate.

[0054] Specifically, the separator comprises a porous polyolefin substrate and a porous coating layer formed on at least one surface of the porous polyolefin substrate, and

[0055] The porous polyolefin substrate comprises a cross-linked polyolefin resin, and the cross-linked polyolefin resin comprises silicon-containing organic groups grafted to polyolefin chains,

[0056] The porous coating layer comprises inorganic particles and a binder polymer, wherein the inorganic particles comprise boehmite (AlO(OH)).

[0057] According to one embodiment of the present invention, the porous polyolefin substrate may comprise a cross-linked polyolefin resin and chromium (Cr).

[0059] First, a porous polyolefin substrate as a separator substrate with improved heat resistance and wetting properties will be described in detail.

[0060] porous polyolefin substrate

[0061] The above porous polyolefin substrate is a separator substrate for an electrochemical device comprising a cross-linked polyolefin resin, wherein the cross-linked polyolefin resin comprises silicon-containing organic groups grafted to polyolefin chains.

[0062] In one embodiment of the present invention, the cross-linked polyolefin resin may contain chromium (Cr) derived therefrom by using a chromium (Cr)-containing catalyst during the production of the polyolefin, but the present invention is not limited thereto.

[0063] In one embodiment of the present invention, the porous polyolefin substrate may have a gel fraction of 3% to 80%.

[0064] In one embodiment of the present invention, the porous polyolefin substrate may have a standard deviation (△d) of thickness measured at any 100 points of 0.5 μm or less.

[0065] In another embodiment of the present invention, the porous polyolefin substrate may have a gel fraction of 3% to 80% and a standard deviation (△d) of thickness measured at any 100 points of 0.5 μm or less.

[0066] In one embodiment of the present invention, the porous polyolefin substrate is 1 m 2 The number of spots with a long side length of 50 μm or more may be 10 or fewer.

[0067] In another embodiment of the present invention, the porous polyolefin substrate has a gel fraction of 3% to 80%, a standard deviation (△d) of thickness measured at any at least 100 points of 0.5 or less, and 1 m 2 The number of spots with a long side length of 50 μm or more may be 10 or fewer.

[0068] According to one embodiment of the present invention, the polyolefin resin is used as a porous separator substrate and is not particularly limited to the monomer thereof, but for example, the polyolefin resin may be a homopolymer of a monomer selected from polyethylene, polypropylene, polybutylene, polypentene, polyhexene, polyoctene, ethylene, propylene, butene, pentene, 4-methylpentene, hexene, and octene; a copolymer of two or more of these; or a mixture thereof, but is not limited thereto.

[0069] As described below in the method for manufacturing the porous polyolefin substrate in this specification, the porous polyolefin substrate may contain chromium (Cr) by including a polyolefin resin prepared using an olefin polymerization catalyst containing chromium (Cr). Specifically, the porous polyolefin substrate contains chromium as a residue of the chromium catalyst used in the polymerization of the polyolefin resin.

[0070] In one embodiment of the present invention, the chromium-containing olefin polymerization catalyst may comprise, for example, chromium oxide; and a support supporting the chromium oxide; wherein the support may comprise, for example, at least one component selected from silica, titania, alumina, zirconia, and aluminum phosphate, but the present invention is not limited thereto.

[0071] In one embodiment of the present invention, the chromium content contained in the porous polyolefin substrate may be, for example, 0.1 to 20 ppm, 1 to 10 ppm, or 5 to 10 ppm, but is not limited thereto. The chromium content in the porous polyolefin substrate may be, for example, a value measured using an inductively coupled plasma with mass spectrometer (ICP-MS). When the chromium content contained in the porous polyolefin substrate is within the range described above, there may be advantageous effects in terms of the number of vinyl groups in the polyolefin resin before crosslinking and the degree of crosslinking of the crosslinked polyolefin resin prepared using the same, but the present invention is not limited thereto.

[0072] According to one embodiment of the present invention, a polyolefin resin prepared using the chromium-containing olefin polymerization catalyst is characterized by containing a large amount of active terminal vinyl groups capable of crosslinking by a thermal initiator contained in a coating solution in a subsequent process. Accordingly, the porous polyolefin substrate may comprise a polyolefin resin in which a plurality of crosslinked structures between polyolefin chains are formed by a crosslinking reaction by a thermal initiator.

[0073] In addition, according to one embodiment of the present invention, a polyolefin resin prepared using the chromium-containing olefin polymerization catalyst is characterized by containing a large amount of active terminal vinyl groups that provide a site for grafting a vinyl group-containing silane compound contained in a coating solution in a subsequent process. Thus, the porous polyolefin substrate may contain silicon-containing organic groups through which a plurality of vinyl group-containing silane compounds are grafted via the terminal vinyl groups.

[0074] In one embodiment of the present invention, a silicon-containing organic group grafted to the polyolefin chain is present on the surface of the porous polyolefin substrate, thereby imparting polarity to the surface of the porous polyolefin substrate and improving the chemical affinity with inorganic particles within the porous coating layer formed on the porous polyolefin substrate.

[0075] In this specification, the 'crosslinked polyolefin resin' refers to a polyolefin resin in which a vinyl group present within the chain of the polyolefin resin, used as a raw material for a porous polyolefin substrate, is activated by an initiation reaction, thereby forming a crosslinked structure within and / or between the chains of the polyolefin resin.

[0076] Specifically, the cross-linked polyolefin resin is formed by the activation of a vinyl group at one end of the polyolefin chain by a thermal initiator to form a radical, and the formed radical undergoes a polymerization reaction with a radical formed in the polyolefin chain of another molecule and / or a radical formed at the other end of the polyolefin chain of the same molecule, thereby C(Sp 2 )- C(Sp 2 It may include a combined cross-linked structure.

[0077] In addition, in one embodiment of the present invention, the 'silicon-containing organic group grafted to the polyolefin chain' may represent a residue derived from the vinyl group-containing silane compound by activating the vinyl group present in the chain of the polyolefin resin used as a raw material for the porous polyolefin substrate and the vinyl group present in the vinyl group-containing silane compound through an initiation reaction, and forming a new covalent bond at the activated position.

[0078] In one embodiment of the present invention, the silicon-containing organic group represents an organic residue derived from the vinyl group-containing silane compound, and the vinyl group-containing silane compound may include, for example, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltriacetoxysilane, (3-methacryloxypropyl)trimethoxysilane, (3-methacryloxypropyl)triethoxysilane, vinylmethyldimethoxysilane, vinyl-tris(2-methoxyethoxy)silane, vinylmethyldiethoxysilane, or a mixture of two or more of these, but the present invention is not limited thereto.

[0079] In one embodiment of the present invention, the crosslinked polyolefin resin may not contain any terminal vinyl groups, or may contain a reduced number of terminal vinyl groups compared to the number of terminal vinyl groups present in the polyolefin resin prior to crosslinking.

[0080] In a similar respect, the cross-linked polyolefin resin is C (Sp) contained in the polyolefin resin prior to cross-linking. 2 )- C(Sp 2 A number of C(Sp) increased compared to the number of ) bonds 2 )- C(Sp 2 It may contain ) bonds.

[0081] In one embodiment of the present invention, the polyolefin resin prepared using the chromium-containing olefin polymerization catalyst may contain at least 100, at least 200, at least 300, at least 400, at least 500, at least 600, at least 700, at least 800, at least 900, or at least 950 terminal vinyl groups per million carbons when the number of functional groups is determined from the 1H-NMR spectrum results using a nuclear magnetic resonance spectrometer (Bruker 500 NMR, 14.1 telsa). The upper limit of the terminal vinyl groups may be 1,500 or less or 1,000 or less within the above-described range, but is not limited thereto.

[0082] Accordingly, in one embodiment of the present invention, the number of terminal vinyl groups of the polyolefin resin prior to crosslinking may be, for example, 100 or more, 200 or more, 300 or more, 400 or more, 500 or more, 600 or more, 700 or more, 800 or more, 900 or more, or 950 or more per million carbons.

[0083] In another embodiment of the present invention, when the porous polyolefin substrate comprises a polyolefin resin prepared using a catalyst other than a chromium-containing olefin polymerization catalyst, it is preferable that the number of terminal vinyl groups of the polyolefin resin before crosslinking and the content of terminal vinyl groups of the polyolefin resin before crosslinking be measured based on the number of terminal vinyl groups and the content of terminal vinyl groups of the total polyolefin resin.

[0084] As described above, the crosslinked structure within the crosslinked polyolefin resin comprises a structure derived from the result of a radical polymerization reaction between vinyl groups mediated by a thermal initiator.

[0085] In one embodiment of the present invention, the thermal initiator may be used without limitation as long as it is an initiator capable of forming radicals by activating vinyl groups present in the polyolefin chain. Specifically, any initiator capable of forming radicals by activating terminal vinyl groups present in the polyolefin chain may be used without limitation. The thermal initiator may include, for example, a peroxide-based compound, a persulfate-based compound, an azo-based compound, or a mixture thereof.

[0086] The above peroxide-based compounds may include, for example, 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexane (2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, DHBP), benzoyl peroxide, acetyl peroxide, dilauryl peroxide, di-tert-butyl peroxide, dicumyl peroxide, cumyl peroxide, hydrogen peroxide, or a mixture of two or more of these, but are not limited thereto.

[0087] The above persulfate-based compound is a peroxymonosulfate ion (SO5) as an anion. 2- ) and peroxydisulfate (S2O8 2-Compounds comprising at least one of the following are not particularly limited. Examples of the persulfate compounds include, but are not limited to, sodium peroxymonosulfate (Na2SO5), potassium peroxymonosulfate (KHSO5), sodium peroxydisulfate (Na2S2O8), ammonium peroxydisulfate ((NH4)2S2O8), potassium peroxydisulfate (K2S2O8), or a mixture of two or more of these.

[0088] The above azo compounds may include, for example, 2,2'-azobis(2-methylpropionitrile) (2,2'-azobis(2-methylpropionitrile, AIBN), but are not limited thereto.

[0089] In one embodiment of the present invention, the porous polyolefin substrate may further include a polyolefin resin produced from a different type of olefin polymerization catalyst in addition to the polyolefin resin produced from a chromium-containing olefin polymerization catalyst as described above.

[0090] The above-mentioned other type of olefin polymerization catalyst may be an olefin polymerization catalyst containing, for example, at least one of titanium (Ti), aluminum (Al), magnesium (Mg), zirconium (Zr), and vanadium (V). Accordingly, the membrane substrate may further include, for example, at least one of titanium (Ti), aluminum (Al), magnesium (Mg), zirconium (Zr), and vanadium (V).

[0091] In one embodiment of the present invention, the other type of olefin polymerization catalyst may be, for example, a metallocene catalyst, a Ziegler catalyst, or a mixture thereof, but the present invention is not limited thereto.

[0092] In this specification, a polyolefin resin produced using the chromium-containing olefin polymerization catalyst may be referred to as a 'Cr-type polyolefin,' and a polyolefin resin produced using the other type of olefin polymerization catalyst may be referred to as a 'ZT-type polyolefin.'

[0093] In one embodiment of the present invention, when the porous polyolefin substrate comprises a polyolefin resin prepared using a different type of olefin polymerization catalyst in addition to a polyolefin resin prepared using a chromium-containing olefin polymerization catalyst, the weight ratio of the Cr-type polyolefin and the ZT-type polyolefin may be, for example, 1:9 to 9:1, specifically 2:8 to 8:2, 3:7 to 7:3, or 5:5, but is not limited thereto. When the separator substrate comprises both the Cr-type polyolefin and the ZT-type polyolefin, there may be an advantageous effect in that the molecular weight of the separator substrate can be improved by the ZT-type polyolefin with a high molecular weight, but the present invention is not limited thereto.

[0094] In one embodiment of the present invention, the separator may further include at least one of polymer resins such as polyethylene terephthalate, polybutylene terephthalate, polyacetal, polyamide, polycarbonate, polyimide, polyetheretherketone, polyethersulfone, polyphenylene oxide, polyphenylene sulfide, and polyethylene naphthalene as a raw material for the separator substrate, in addition to a polyolefin material. Furthermore, the porous polyolefin substrate may be a nonwoven fabric, a porous polymer film, or a laminate of two or more of these, but is not particularly limited thereto.

[0095] In one embodiment of the present invention, as described below, the porous polyolefin substrate comprises a polyolefin resin produced using a chromium-containing olefin polymerization catalyst, and when a polyolefin sheet derived from the polyolefin resin is heat-set during the manufacturing process of a separator substrate, a cross-linked structure is formed within and / or between chains of the polyolefin resin by a radical polymerization reaction mediated by the heat initiator, thereby improving the thickness uniformity and heat resistance of the porous polyolefin substrate, as well as improving the appearance characteristics of the porous polyolefin substrate. In addition, when the polyolefin sheet derived from the polyolefin resin is heat-set, the vinyl group-containing silane compound is grafted, thereby improving the wettability of the porous polyolefin substrate, but the mechanism of the present invention is not limited thereto.

[0096] According to one embodiment of the present invention, the porous polyolefin substrate exhibits a gel fraction of 3% to 80%. This may be a characteristic resulting from the porous polyolefin substrate including a polyolefin resin with excellent crosslinking degree, but the characteristics of the present invention are not limited thereto. The gel fraction of the porous polyolefin substrate may be, for example, 3% to 70%, 3% to 60%, 3% to 50%, 3% to 45%, 3% to 40%, 3% to 30%, 3% to 20%, or 3% to 10%.

[0097] As described above, one feature of the polyolefin resin is that it exhibits a high degree of crosslinking due to a crosslinking structure formed within and / or between the polyolefin chains. Accordingly, while the polyolefin resin before crosslinking is soluble in a benzene-based solvent, the crosslinked polyolefin resin may exhibit characteristics in which it is not soluble in a benzene-based solvent and the gel fraction is measured.

[0098] In this specification, the gel fraction may be measured according to the following method. First, 0.2 g of the membrane substrate specimen to be measured is placed in a 120-mesh stainless steel mesh, extracted in trichlorobenzene at 100°C for 12 hours, and then dried in a vacuum oven at 100°C for 12 hours. Afterward, the weight of the specimen remaining on the stainless steel mesh is measured, and the gel fraction is measured according to the following formula. To improve the accuracy of the measurement value, the gel fraction may represent the average value of the measurements for three specimens.

[0099] Gel fraction (%) = {(Weight of remaining specimen g) / 0.2 g} X 100

[0100] In one embodiment of the present invention, the porous polyolefin substrate has a standard deviation (△d) of thickness measured at at least 100 points of any thickness of 0.5 μm or less. By doing so, the separator substrate can exhibit excellent uniformity of thickness.

[0101] In one embodiment of the present invention, the standard deviation (△d) of the thickness measured at any 100 points of the porous polyolefin substrate may be, for example, 0.5 μm or less, 0.45 μm or less, 0.40 μm or less, 0.35 μm or less, 0.3 μm or less, or 0.25 μm or less. Since the thickness uniformity increases as the standard deviation approaches 0, the lower limit of the standard deviation of the thickness may be 0.

[0102] The thickness of the above-mentioned separator substrate may be measured according to a method for measuring the thickness of the separator substrate, for example, by SEM image analysis of the manufactured separator substrate or by a value measured using a known thickness gauge. For example, the VL-50S-B (Mitutoyo) may be used as the thickness gauge, but is not limited thereto.

[0103] Generally, when raw materials such as polymer resins, diluents, crosslinking agents, and other additives are introduced into an extruder and reacted all at once during the manufacture of a separator substrate, side reactions occur within the extruder, or due to insufficient mixing between the raw materials, unmelted raw materials cause spots on the surface of the separator substrate that differ in brightness from the surrounding area.

[0104] In this specification, the 'spot' refers to an area on the surface of a separator substrate that has a white spot shape with high brightness and low transparency compared to the surrounding area.

[0105] In one embodiment of the present invention, the number of spots can be evaluated through visual observation or microscopic observation such as SEM.

[0106] According to one embodiment of the present invention, the porous polyolefin substrate may exhibit improved appearance defects by reducing the amount of spots such as those mentioned above, as a polyolefin resin is introduced as a raw material to form a polyolefin sheet, and then a thermal initiator and a vinyl group-containing silane compound are introduced. For example, the separator substrate is 1 m 2 The number of spots with a long side length of 50 μm or more may be 10 or fewer. Specifically, within the above conditions, the number of spots may be 0 to 7, 0 to 5, 0 to 3, or 0. By forming the number of spots within the above-described range, there may be an advantageous effect in terms of preventing uncoated areas and short circuits within the battery due to appearance defects during subsequent ceramic coating.

[0107] In another embodiment of the present invention, the thickness of the porous polyolefin substrate may be, for example, 4 to 20 μm. When the thickness of the porous polyolefin substrate is within the above-described range, it may exhibit advantageous effects in terms of conductive barrier function and resistance of the separator, but the present invention is not limited thereto.

[0108] In one embodiment of the present invention, the weight-average molecular weight (Mw) of the polyolefin resin included in the porous polyolefin substrate may range, for example, from 100,000 to 5 million. When the weight-average molecular weight of the polyolefin resin is in the range described above, it may exhibit advantageous effects in terms of securing mechanical properties of the separator substrate and shutdown characteristics, but the present invention is not limited thereto.

[0109] In this specification, the weight-average molecular weight (Mw) of the polyolefin resin can be measured by gel permeation chromatography (GPC, PL GPC220, Agilent Technologies) under the following conditions.

[0110] - Column: PL Olexis (Polymer Laboratories)

[0111] - Solvent: TCB (Trichlorobenzene)

[0112] - Flow rate: 1.0 ml / min

[0113] - Sample concentration: 1.0 mg / ml

[0114] - Injection volume: 200 µl

[0115] - Column temperature: 160℃

[0116] - Detector: Agilent High Temperature RI detector

[0117] - Standard: Polystyrene (corrected by a cubic function)

[0118] In one embodiment of the present invention, the porous polyolefin substrate has a structure containing a large amount of micropores, for example, the average diameter of the pores may be 0.01 μm to 0.10 μm and the porosity may be 30% to 70%. When the average diameter and porosity of the pores within the porous polyolefin substrate are within the ranges described above, advantageous effects may be exhibited in terms of ion permeability and mechanical strength of the separation membrane using the same, but the present invention is not limited thereto.

[0119] In one embodiment of the present invention, the porous polyolefin substrate may exhibit excellent heat resistance. For example, the porous polyolefin substrate may exhibit a rupture temperature of 155°C or higher. For example, the rupture temperature of the porous polyolefin substrate may be 160°C or higher, 170°C or higher, 180°C or higher, 190°C or higher, 195°C or higher, and furthermore, 200°C or higher. Since the higher the rupture temperature of the porous polyolefin substrate, the greater the heat resistance, the upper limit of the rupture temperature of the porous polyolefin substrate may not be particularly limited, and exemplarily, it may be 500°C or lower, 450°C or lower, 350°C or lower, or 300°C or lower.

[0120] In this specification, the breaking temperature of the porous polyolefin substrate can be measured using a thermal mechanical analysis (TMA) instrument by applying a load of 0.01 N to a porous polyolefin substrate specimen to be measured and observing the degree of deformation while increasing the temperature at a rate of 5°C / min, and as the temperature rises, the porous polyolefin substrate shrinks and then expands again and breaks.

[0121] In one embodiment of the present invention, the porous polyolefin substrate may have the characteristic of improved wettability by including silicon-containing organic groups grafted to the polyolefin chains as described above.

[0122] In one embodiment of the present invention, the 'wettability' of the porous polyolefin substrate indicates the property of the electrolyte penetrating, and may be evaluated according to a conventional method for evaluating the degree of electrolyte penetration. For example, it may be evaluated by a method of measuring the area over which the electrolyte has spread after a certain amount of electrolyte has been dropped onto the porous polyolefin substrate and a certain amount of time has elapsed. The larger the area over which the dropped electrolyte has spread during the same period of time, the better the wettability with the electrolyte may be evaluated.

[0123] The porous polyolefin substrate described above may have the effect of improving appearance characteristics, thickness uniformity, heat resistance, and wettability by forming a cross-linked structure between polyolefin chains through the use of a heat initiator and a vinyl group-containing silane compound during the heat setting of a polyolefin sheet stretched from the polyolefin resin, and by including grafted silicon-containing organic groups, but the present invention is not limited thereto.

[0125] Next, the porous polyolefin substrate described above and the porous coating layer with excellent adhesion will be explained in detail.

[0126] porous coating layer

[0127] The above-mentioned porous coating layer comprises a binder resin and inorganic particles, has a plurality of micropores inside, and is structured such that these micropores are interconnected, and has the structural characteristics of a porous layer that allows gas or liquid to pass from one side to the other.

[0128] In one embodiment of the present invention, the porous coating layer may have a porous structure derived from pores resulting from the interstitial volume between inorganic particles. The size or porosity (ratio of pore volume) of the pores can be controlled according to the particle size and size distribution. Through this structure, resistance to metallic foreign substances present on the electrode is increased, and at the same time, shrinkage of the porous polyolefin substrate is suppressed, thereby enhancing the safety of the electrochemical device.

[0129] In one embodiment of the present invention, the porous coating layer comprises a plurality of nodes including a binder polymer covering at least a portion of the surface of the inorganic particles and the inorganic particles; and one or more filaments formed in a thread shape from the binder polymer of the nodes, wherein the filaments have a node connecting portion extending from the nodes to connect other nodes, and the node connecting portion may have a structure in which a plurality of filaments derived from the binder polymer intersect each other to form a three-dimensional network structure.

[0130] In one embodiment of the present invention, as described above, the porous coating layer may be formed through an SRS (Safety Reinforced Separator) manufacturing method, a CCS (Ceramic Coated Separator) manufacturing method, or other known manufacturing methods.

[0131] As described above, according to one embodiment of the present invention, the porous polyolefin substrate may exhibit improved wetting properties by including silicon-containing organic groups grafted to the polyolefin chains. In particular, the silicon-containing organic groups grafted to the polyolefin chains are present on the surface of the porous polyolefin substrate, thereby imparting polarity to the surface of the porous polyolefin substrate and improving the chemical affinity with inorganic particles within the porous coating layer formed on the porous polyolefin substrate.

[0132] According to one aspect of the present invention, by providing a porous coating layer with particularly improved adhesion to a porous polyolefin substrate with improved wetting properties as described above, excellent properties can be exhibited without limitation on the manufacturing method of the separator, and the effect of improving the properties of electrochemical irradiation using the same can be achieved.

[0133] To this end, the porous coating layer comprises boehmite (AlO(OH)) as an inorganic particle.

[0134] According to one embodiment of the present invention, the -OH functional group of the boehmite may exhibit the advantage of excellent adhesion to the porous polyolefin substrate of the present invention among aluminum-containing inorganic particles, but the present invention is not limited thereto.

[0135] According to one embodiment of the present invention, the separator may exhibit an adhesion strength between the porous polyolefin substrate and the porous coating layer of, for example, 50 gf / 15 mm or more. Specifically, the adhesion strength between the porous polyolefin substrate and the porous coating layer may be 50 to 100 gf / 15 mm, 50 to 95 gf / 15 mm, 55 to 95 gf / 15 mm, 60 to 95 gf / 15 mm, 65 to 95 gf / 15 mm, 70 to 95 gf / 15 mm, 75 to 90 gf / 15 mm, or 80 to 85 gf / 15 mm. When the adhesion strength between the porous polyolefin substrate and the porous coating layer is within the above-described range, it may exhibit an advantageous effect for improving the performance of an electrochemical device using the separator, but the present invention is not limited thereto.

[0136] In this specification, the adhesion strength between the porous polyolefin substrate and the porous coating layer may be measured according to a known method for measuring the peel strength between the porous polyolefin substrate and the porous coating layer, for example, by the following method. Double-sided adhesive tape is attached to a glass plate, and a separator to be measured, cut to a size of 15 mm x 100 mm, is attached so that the surface of the porous coating layer adheres to the adhesive tape. Afterward, the end of the attached separator is mounted on a UTM device, and a force is applied at an angle of 180° at a measurement speed of 300 mm / min to measure the force required to peel off the separator substrate and the porous coating layer. At this time, the UTM device used is not particularly limited, and for example, the LLOYD Instrument LF Plus may be used.

[0137] In one embodiment of the present invention, in order to exhibit excellent adhesion to a separator substrate, the porous coating layer comprises boehmite (AlO(OH)) as an inorganic particle, and specifically, the content of the boehmite may be, for example, 80 wt% or more based on the total weight of the inorganic particles included in the porous coating layer. More specifically, the content of the boehmite may be, for example, 80 wt% to 100 wt%, 85 wt% to 99 wt%, 90 wt% to 95 wt%, 95 wt% to 99 wt%, or 95 wt% to 100 wt% based on the total weight of the inorganic particles included in the porous coating layer, but the present invention is not limited thereto.

[0138] In another embodiment of the present invention, the porous coating layer may further include conventional inorganic particles other than boehmite used in porous coating layers, as inorganic particles, to the extent that such particles do not impede the purpose of the present invention.

[0139] The inorganic particles that may be further included are not particularly limited, provided they are, for example, electrochemically stable. That is, the inorganic particles that may be further included in the present invention may not be particularly limited as long as they do not undergo oxidation and / or reduction reactions within the operating voltage range of the applied electrochemical device (e.g., 0 to 5 V based on Li / Li+). In particular, if inorganic particles with a high dielectric constant are further used as inorganic particles, they can contribute to increasing the degree of dissociation of electrolyte salts, such as lithium salts, within the liquid electrolyte, thereby improving the ionic conductivity of the electrolyte.

[0140] In one embodiment of the present invention, the inorganic particles that may be further included are specifically alumina (Al2O3), aluminum hydroxide (Al(OH)3), silica (SiO2), titanium dioxide (TiO2), magnesium oxide (MgO), magnesium hydroxide (Mg(OH)2), zinc oxide (ZnO), barium titanate (BaTiO), aluminum nitride (Al), boron nitride (BN), silicon carbide (SiC), beryllium oxide (BeO), potassium nitrate (KNO3), ammonium dihydrogen phosphate (NH4H2PO4), BaTiO3, Pb(Zr,Ti)O3 (PZT), P 1-x La x Zr 1-y Ti y O3(PLZT, 0 <x<1, 0<y<1), Pb(Mg 1 / 3 Nb 2 / 3 Examples include O3-PbTiO3 (PMN-PT), hafnia (HfO2), SrTiO3, SnO2, CeO2, NiO, CaO, ZrO2, SiC and TiO2, or a mixture of two or more of these, but the present invention is not limited thereto.

[0141] In one embodiment of the present invention, when other inorganic particles other than boehmite are further included as the inorganic particles, the content of the further included inorganic particles may be, for example, 20 weight% or more, specifically 15 weight% or less, 10 weight% or less, 5 weight% or less, or 1 weight% or less, but the present invention is not limited thereto.

[0142] In one embodiment of the present invention, the average particle size (D) of the inorganic particles 50 Although there are no specific limitations, for the formation of a porous coating layer of uniform thickness and appropriate porosity, it may be preferable to be in the range of 0.01㎛ to 2㎛, specifically in the range of 0.5㎛ to 1㎛.

[0143] In one embodiment of the present invention, the binder material may include an acrylic polymer and a PVDF-based polymer, or a mixture thereof.

[0144] The above acrylic polymer may include, for example, a (meth)acrylic polymer. The above (meth)acrylic polymer contains (meth)acrylic acid esters as monomers, and examples of such monomers may include butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, ethyl (meth)acrylate, methyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, n-oxyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, lauryl (meth)acrylate, tetradecyl (meth)acrylate, etc., and may include one or more of these.

[0145] In one embodiment of the present invention, the acrylic polymer may include styrene-butyl acrylate.

[0146] According to one embodiment of the present invention, the acrylic polymer may include, for example, a glass transition temperature (Tg) of 0°C to 80°C, specifically 20°C to 60°C, 30°C to 50°C, 35°C to 45°C, or 40°C to 45°C. When the glass transition temperature of the binder material is within the range described above, excellent effects may be exhibited in terms of air permeability and adhesion of the porous coating layer, but the present invention is not limited thereto.

[0147] The above PVdF-based polymer may comprise one or more of a homopolymer of vinylidene fluoride (i.e., polyvinylidene fluoride), a copolymer with a monomer capable of copolymerizing with vinylidene fluoride, and a mixture thereof. In one embodiment of the present invention, the monomer may be, for example, a fluorinated monomer and / or a chlorinated monomer. Non-limiting examples of the fluorinated monomer include vinyl fluoride; trifluoroethylene (TrFE); chlorofluoroethylene (CTFE); 1,2-difluoroethylene; tetrafluoroethylene (TFE); hexafluoropropylene (HFP); perfluoro(alkylvinyl) ethers such as perfluoro(methylvinyl) ether (PMVE), perfluoro(ethylvinyl) ether (PEVE), and perfluoro(propylvinyl) ether (PPVE); and perfluoro(1,3-dioxol). and perfluoro(2,2-dimethyl-1,3-dioxol) (PDD), etc., and one or more of these may be included.

[0148] In one embodiment of the present invention, the PVDF-based polymer may include one or more selected from polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyvinylidene fluoride-chlorofluoroethylene (PVDF-CTFE), polyvinylidene fluoride-tetrafluoroethylene (PVdF-TFE), and polyvinylidene fluoride-trifluoroethylene (PVdF-TrFE).

[0149] According to one embodiment of the present invention, the PVDF-based polymer may include, for example, a glass transition temperature (Tg) of -80°C to 0°C, specifically -60°C to -20°C, -50°C to -30°C, -45°C to -35°C, or -45°C to -40°C.

[0150] When the glass transition temperature of the above-described binder material is within the range described above, excellent effects can be exhibited in terms of air permeability and adhesion of the porous coating layer, but the present invention is not limited thereto.

[0151] In this specification, the glass transition temperature may be measured by a conventional method for measuring the glass transition temperature of a polymer material, for example, by using Differential Scanning Calorimetry (DSC) in accordance with ISO 1135762. Specifically, a graph regarding the relationship between the temperature of a sample and the heat flow supplied is obtained while causing a temperature change in the DSC sample, and the glass transition temperature can be measured at the point where the graph intersects when two extension lines are connected, which are extension lines of the graph before and after the change at the point where the slope of the graph changes abruptly. At this time, the temperature change may be performed once or repeatedly by raising and lowering the temperature at a constant rate of 0.01°C to 100°C, for example, at a rate of 10°C / min, within the range of -80°C to 500°C.

[0153] According to another aspect of the present invention, a method for manufacturing a separation membrane having the above-described configuration is provided.

[0154] Method for manufacturing a separator for an electrochemical device

[0155] First, according to one embodiment of the present invention, the porous polyolefin substrate used in the separator can be manufactured according to the following method.

[0156] The method for manufacturing the above-described porous polyolefin substrate may include, for example, a step of obtaining a polymer melt extruded product by melt-extruding a raw material containing a polyolefin resin; a step of obtaining a polymer sheet by molding and stretching the obtained polymer melt extruded product; a step of applying a coating solution containing a thermal initiator and a vinyl group-containing silane compound to the polymer sheet; and a step of drying and heat-setting the polymer sheet coated with the coating solution. The polyolefin resin includes a polyolefin resin prepared using an olefin polymerization catalyst containing chromium.

[0157] First, a raw material containing a polyolefin resin prepared using the chromium-containing olefin polymerization catalyst is melt-extruded to obtain a polymer melt extruded product.

[0158] In one embodiment of the present invention, for the melt extrusion, the raw material preferably comprises a polyolefin resin prepared using the chromium-containing olefin polymerization catalyst as well as a diluent.

[0159] The above diluent may be, for example, liquid or solid paraffin oil, mineral oil, wax, soybean oil, etc., which are commonly used in the manufacture of wet separation membranes.

[0160] In one embodiment of the present invention, the diluent may be a diluent capable of liquid-liquid phase separation with the polyolefin resin, for example, phthalic acid esters such as dibutyl phthalate, dihexyl phthalate, dioctyl phthalate; aromatic ethers such as diphenyl ether and benzyl ether; fatty acids having 10 to 20 carbon atoms such as palmitic acid, stearic acid, oleic acid, linoleic acid, and linolenic acid; fatty acid alcohols having 10 to 20 carbon atoms such as palmitic acid alcohol, stearic acid alcohol, and oleic acid alcohol; palmitic acid mono-, di-, or triester, stearic acid mono-, di-, or triester. Saturated and unsaturated fatty acids having 4 to 26 carbon atoms in a fatty acid group such as oleic acid mono-, di-, or triester, linoleic acid mono-, di-, or triester, or one or more fatty acids in which the double bond of the unsaturated fatty acid is substituted with an epoxy group, are esterified with an alcohol having 1 to 8 hydroxyl groups and 1 to 10 carbon atoms; or a mixture of two or more of these may be used, but is not limited thereto.

[0161] In one embodiment of the present invention, the content of the diluent may be, for example, 100 to 350 parts by weight, 125 to 300 parts by weight, or 150 to 250 parts by weight based on 100 parts by weight of the polyolefin. When the total content of the diluent satisfies the above numerical range, problems such as reduced porosity and smaller pore size and less interconnectedness between pores resulting in significantly lower permeability as the polyolefin content increases, and increased viscosity of the polyolefin composition resulting in increased extrusion load and difficulty in processing can be prevented. Additionally, problems such as fracture during stretching and non-uniform thickness occurring when the polyolefin is extruded in a gel form without being thermodynamically mixed with the diluent due to reduced mixing ability between the polyolefin and the diluent as the polyolefin content is low can be prevented, but the present invention is not limited thereto.

[0162] In one embodiment of the present invention, the raw material may further include a polyolefin resin and other polymer resins prepared using a polyolefin polymerization catalyst containing chromium, in addition to a diluent and other types of olefin polymerization catalysts, such as a Ziegler-Natta catalyst; or an olefin polymerization catalyst containing titanium (Ti), aluminum (Al), magnesium (Mg), zirconium (Zr), vanadium (V), or two or more of these, and the above description is applied to these polyolefin resins and other polymer resins.

[0163] For example, in one embodiment of the present invention, the raw material may further include a polyolefin resin produced by an olefin polymerization reaction using a Ziegler-Natta catalyst.

[0164] According to one embodiment of the present invention, the weight ratio of a polyolefin resin (Cr-type polyolefin) produced using an olefin polymerization catalyst containing chromium among the raw materials and a polyolefin resin (ZT-type polyolefin) produced using another type of olefin polymerization catalyst may be 1:9 to 9:1, specifically 2:8 to 8:2, 3:7 to 7:3, or 5:5, but the present invention is not limited thereto.

[0165] According to another embodiment of the present invention, when a ZT-type polyolefin is further included in addition to the Cr-type polyolefin, the content of the polyolefin resin produced using the chromium-containing olefin polymerization catalyst may be, for example, 10 weight% or more based on 100 weight% of the total raw materials. Specifically, based on 100 weight% of the total raw materials, the content of the polyolefin resin produced using the chromium-containing olefin polymerization catalyst may be 15 weight% or more, 20 weight% or more, 25 weight% or less, 30 weight% or more, 35 weight% or more, 40 weight% or more, 45 weight% or more, 50 weight% or more, and / or 99.9 weight% or less, 99 weight% or less, 95 weight% or less, or 90 weight% or less, but the present invention is not limited thereto.

[0166] In one embodiment of the present invention, the step of obtaining the polymer melt extruded product may use a conventional single-screw extruder or a twin-screw extruder, but is not limited thereto.

[0167] Next, the obtained polymer melt extruded material is molded and stretched to obtain a polymer sheet.

[0168] In one embodiment of the present invention, after the extrusion of the polymer melt extruder, a cooled extruder can be formed using a conventional casting or calendering method, such as water cooling or air cooling.

[0169] In one embodiment of the present invention, a separation membrane substrate having improved mechanical strength and puncture strength can be provided by undergoing the molding and stretching steps.

[0170] In one embodiment of the present invention, the stretching may be performed by a roll method or a tender method, sequentially, or simultaneously. The stretching ratio may be, for example, 3 times or more, or 5 to 12 times in the longitudinal and transverse directions, respectively, and the total stretching ratio may be 20 to 120 times. When the stretching ratio satisfies the above numerical range, there may be advantageous effects in terms of thickness uniformity of the manufactured separator substrate and balance of physical properties between the longitudinal and transverse directions, but the present invention is not limited thereto.

[0171] In one embodiment of the present invention, the stretching temperature may vary depending on the melting point of the polyolefin resin used, the concentration and type of diluent, and the present invention is not limited thereto.

[0172] Subsequently, a diluent is extracted from the stretched polymer sheet to obtain a porous polymer sheet.

[0173] In one embodiment of the present invention, a porous sheet can be formed by extracting and drying the diluent using an organic solvent that is highly soluble in the diluent on the stretched sheet.

[0174] The above organic solvent is not particularly limited as long as it can extract the diluent used, but methyl ethyl ketone, methylene chloride, hexane, etc. may be used in terms of extraction efficiency and drying speed.

[0175] In one embodiment of the present invention, the extraction method may utilize any general solvent extraction method, such as an immersion method, a solvent spray method, or an ultrasonic method, either individually or in combination. In one embodiment of the present invention, the content of residual diluent after the extraction treatment may preferably be 1 weight% or less. When the content of residual diluent is within the range described above, it may exhibit advantageous effects in terms of the permeability and mechanical properties of the membrane substrate manufactured and the efficiency of the manufacturing process, but the present invention is not limited thereto. The extraction time and extraction temperature may vary depending on the thickness of the polymer sheet and the type of polymer, and the present invention is not limited thereto.

[0176] Next, a coating solution containing a thermal initiator and a vinyl group-containing silane compound is applied to the polymer sheet.

[0177] According to one embodiment of the present invention, a coating solution comprising a thermal initiator and a vinyl group-containing silane compound is applied to a polymer porous sheet in which pores are already exposed. As described above, the thermal initiator can activate terminal vinyl groups within the chain of a polyolefin resin to form radicals. Accordingly, not only is a large amount of cross-linked structure formed within the polyolefin chain by the thermal initiator, but the coating solution can also penetrate to the fibrils present on the surface of the already formed pores, and can exhibit excellent effects in terms of improving the heat resistance of the separator substrate, but the present invention is not limited thereto. Furthermore, the vinyl group-containing silane compound may be included by grafting a silicon-containing organic group through covalent bonding to the site where the terminal vinyl group within the chain of the polyolefin resin is activated. Accordingly, it can exhibit excellent effects in terms of improving the wettability of the separator substrate, but the present invention is not limited thereto.

[0178] In one embodiment of the present invention, the thermal initiator and the vinyl group-containing silane compound in the coating solution may be included in a weight ratio of, for example, 2:8 to 8:2, specifically 3:7 to 7:3 or 4:6 to 6:4. When the weight ratio of the thermal initiator and the vinyl group-containing silane compound is within the range described above, the vinyl groups within the chains of the polyolefin resin can be sufficiently activated to induce crosslinking and grafting reactions, and an advantageous effect can be exhibited in terms of improving the wettability of the separator substrate, but the present invention is not limited thereto.

[0179] In one embodiment of the present invention, the coating solution may include, for example, ethanol, propanol, acetone, NMP, DMAC, DMF, water, or a mixture of two or more of these as a solvent for the thermal initiator and the vinyl group-containing silane compound. Additionally, the total content of solids in the coating solution may be, for example, 5% to 60% by weight, specifically 7% to 40% by weight, which may be preferable in terms of radical activation of double bonds and improvement of wettability of the membrane substrate, but the present invention is not limited thereto.

[0180] In one embodiment of the present invention, the coating solution may further include general additives for enhancing specific functions, such as surfactants, oxidation stabilizers, UV stabilizers, antistatic agents, and nucleating agents, as needed, but the present invention is not limited thereto.

[0181] Subsequently, the polymer sheet coated with the above coating solution is dried and heat-set to obtain a separator substrate.

[0182] The above heat fixation is intended to fix the porous membrane and apply heat to forcibly hold the porous membrane attempting to shrink, thereby relieving residual stress.

[0183] According to the method for manufacturing the above-described separator substrate, a coating solution containing the above-described thermal initiator and a vinyl group-containing silane compound is applied before heat setting, thereby forming a large amount of cross-linked structure through a cross-linking reaction within and / or between the polyolefin chains by a radical polymerization reaction mediated by the thermal initiator during heat setting, and a porous polyolefin substrate based on a polyolefin resin in which a large amount of silicon-containing organic groups are grafted to the ends of the polyolefin chains can be obtained.

[0184] In one embodiment of the present invention, the heat-setting temperature and time may vary depending on the vinyl group content in the polyolefin chain and the composition of the coating solution, and the present invention is not limited thereto.

[0186] Next, according to one embodiment of the present invention, the porous coating layer used in the separation membrane as described above can be manufactured by an SRS manufacturing method, a CCS manufacturing method, or other known methods.

[0187] In one embodiment of the present invention, the porous coating layer can be manufactured according to the following method.

[0188] First, the binder material described above is dispersed or dissolved in a solvent to prepare a binder dispersion or binder solution. Next, inorganic particles are added to the binder dispersion or binder solution and dispersed to prepare a slurry for forming a porous coating layer.

[0189] In one embodiment of the present invention, the solvent may serve as a solvent that dissolves the binder polymer depending on the type of binder polymer, or it may serve as a dispersion medium that disperses the binder polymer without dissolving it. The solvent may have a solubility index similar to that of the binder polymer to be used and a low boiling point. In this case, uniform mixing and subsequent removal of the solvent may be easy. Non-limiting examples of such solvents may be one or more mixtures selected from the group consisting of water, acetone, tetrahydrofuran, methylene chloride, chloroform, dimethylformamide, N-methyl-2-pyrrolidone (NMP), and cyclohexane.

[0190] In one embodiment of the present invention, the inorganic particles may be added in a state where they have been crushed to have a predetermined average particle size, or the inorganic particles may be added to a slurry in which the binder polymer is dissolved or dispersed, and then the inorganic particles may be crushed and dispersed using a ball mill method or the like while controlling them to have a predetermined average particle size. At this time, the crushing may be performed for 1 to 20 hours, and the average particle size of the crushed inorganic particles may be as described above. Conventional methods may be used as the crushing method, and a ball mill method may be used.

[0191] In one embodiment of the present invention, the solid content of the slurry for forming the porous coating layer may be 5% to 60% by weight, or 30% to 50% by weight. When the solid content of the slurry for forming the porous coating layer is within the aforementioned range, it may be easy to ensure coating uniformity and easy to prevent non-uniformity from occurring due to slurry flow or to prevent the slurry from requiring a large amount of energy to dry.

[0192] The method of coating the above-mentioned porous coating layer-forming slurry onto a separator substrate may utilize conventional coating methods known in the art, such as dip coating, die coating, roll coating, comma coating, microgravure coating, doctor blade coating, reverse roll coating, Mayer bar coating, direct roll coating, or a combination thereof. In addition, the above-mentioned drying may be performed using conventional drying methods, such as natural drying or air drying, without any particular limitations.

[0194] electrochemical device

[0195] An electrochemical device according to another aspect of the present invention comprises an anode, a cathode, and a separator interposed between the anode and the cathode, wherein the separator is the separator described above.

[0196] In this specification, since the specific configurations of the anode, cathode, and electrode assembly may be conventional, a description thereof will be omitted.

[0197] According to another aspect of the present invention, an electrode assembly comprising a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode can be prepared, and a secondary battery can be provided by loading the electrode assembly prepared as above into a suitable case and injecting an electrolyte.

[0199] The present invention will be described in more detail below through examples, but the following examples are intended to illustrate the invention and the scope of the invention is not limited thereto.

[0201] [Manufacture of porous polyolefin substrates]

[0202] Preparation Example

[0203] 9 kg / hr of Cr-type polyolefin (DL Chemical, TR570) and 21 kg / hr of diluent (Kukdong Yuhwa LP350F) were fed as raw materials into an extruder (Korea EM, φ32 twin-screw extruder L / D=56) and melt-extruded at 200°C to obtain a polyolefin melt extruder. The obtained polyolefin melt extruder was passed through a T-die, formed into a sheet using a cooling casting device, and then biaxially stretched using a tenter-type sequential stretcher with MD stretching followed by TD stretching to obtain a polyolefin sheet. The MD stretching ratio and TD stretching ratio were set to 7 times and 6 times, respectively, and the stretching temperatures were 115°C for MD and 125°C for TD. The diluent was extracted from the stretched polyolefin sheet using methylene chloride to obtain a porous polyolefin sheet.

[0204] Next, a coating solution containing 10 wt% of dicumyl peroxide as a thermal initiator and 20 wt% of vinyltrimethoxysilane as a vinyl group-containing silane compound (wetting agent) was applied to one side of the porous polyolefin sheet.

[0205] Subsequently, a polyolefin sheet coated with the above coating solution was dried and heat-set at 128°C to produce a separator substrate. At this time, the average thickness of the obtained separator substrate was 9.0 μm.

[0207] Comparative Manufacturing Example

[0208] 9 kg / hr of ZT-type polyolefin (Daehan Oil & Chemical, VH035) as raw material and 21 kg / hr of liquid paraffin oil (Kukdong Oil & Chemical LP350F) as diluent were fed into an extruder (Korea EM, φ32 twin-screw extruder L / D=56) and melt-extruded at 200°C to obtain a polyolefin melt extruder.

[0209] The obtained polyolefin molten extruded material was passed through a T-die and formed into a sheet using a cooling casting device. Subsequently, a polyolefin sheet was obtained by biaxial stretching using a tenter-type sequential stretching machine with MD stretching followed by TD stretching. The MD stretching ratio and TD stretching ratio were set to 7 times and 6 times, respectively, and the stretching temperatures were 115℃ for MD and 125℃ for TD.

[0210] A porous polyolefin sheet was obtained by extracting a diluent from the above-mentioned stretched polyolefin sheet using methylene chloride, and then drying and heat-setting it at 128°C to prepare a separator substrate. At this time, the average thickness of the obtained separator substrate was 9.0 μm.

[0212] [Evaluation of Physical Properties of Porous Polyolefin Substrates]

[0213] Measurement of gel fraction

[0214] First, 0.2 g of the membrane substrate sample was placed in a 120-mesh stainless steel mesh, extracted in trichlorobenzene at 100°C for 12 hours, and then dried in a vacuum oven at 100°C for 12 hours.

[0215] Subsequently, the weight of the specimen remaining on the stainless steel mesh was measured, and the gel fraction was determined according to the following formula. The gel fraction was expressed as the average value of the measurements for each of the three specimens.

[0216] Gel fraction (%) = {(Weight of remaining specimen g) / 0.2 g} X 100

[0218] Measurement of chromium (Cr), silicon (Si), and aluminum (Al) content

[0219] First, the membrane substrate specimen was reacted with sulfuric acid and sulfated on a hot plate, after which the sulfuric acid was removed. Subsequently, it was incinerated in an electric furnace (temperature: 600°C) for 4 hours and then decomposed with nitric acid and hydrogen peroxide. Afterward, once the specimen dissolved clearly, it was diluted with tertiary ultrapure water to prepare the analysis sample.

[0220] The chromium (Cr), silicon (Si), and aluminum (Al) content in the membrane substrate was measured using an inductively coupled plasma mass spectrometer (ICP-MS) (Axiom MC model, Thermo Elemental Ltd, UK).

[0221] When using a Ziegler-Natta catalyst, aluminum (Al) is present on the membrane substrate, so the detection of aluminum content is intended to confirm the use of the Ziegler-Natta catalyst.

[0223] Fracture temperature

[0224] The fracture temperature of the separator substrate prepared above was analyzed using a thermal mechanical analysis (TMA) instrument (TA Instruments, TMA Q400).

[0225] Specifically, a load of 0.01 N was applied to the above-mentioned separator substrate, and the degree of deformation was observed while raising the temperature at a rate of 5℃ / min. As the temperature rose, the separator substrate contracted and then expanded again, and the temperature at which it broke was measured as the 'break temperature'.

[0227] Measurement of the number of spots

[0228] Separator material 1m 2 The number of spots was measured by visually checking the number of spots with a long side length of 50㎛ or more.

[0230] Thickness uniformity measurement

[0231] The thickness standard deviation was measured using thickness measurements from a total of 100 locations, with measurements taken at 1m intervals of 10cm in the width direction of the separator substrate and 30m intervals of 3m in the length direction.

[0233] Wetness measurement

[0234] After dropping 4 μm of DMC (dimethyl carbonate) onto one surface of a separator substrate, the spread area was measured. Specifically, after dropping the DMC, a photograph of the surface of the separator substrate was taken after a certain period of time, and the spread area of ​​the DMC in the photograph was measured.

[0235] Polyolefin type Gel fraction (%) Cr(ppm) Si(ppm) Al(ppm) Breaking temperature (°C) Number of spots Thickness uniformity (△d) Wetness (Area, mm 2 ) Preparation Example Cr type 45 9 50 Undetected 202 0 0.20 54 Comparative Manufacturing Example ZT type 0 Undetected Undetected 35 151 0 0.69 24

[0236] [Manufacturing of Separator Membranes]

[0237] Example 1

[0238] A porous polyolefin substrate according to the manufacturing example was prepared as a separator substrate.

[0239] A porous coating layer was formed according to the W-SRS (aqueous SRS) manufacturing method as follows. Specifically, styrene-butyl acrylate (Tg 40°C, particle size (D)) was used as the binder polymer in water. 50 ) 500 nm) and PVDF-HFP copolymer (HFP 5 wt%, Tg -40℃, particle size (D 50 ) 500 nm), and as inorganic particles boehmite (AlO(OH), particle size (D 50 A slurry for forming a porous coating layer was prepared by adding 500 nm) in a weight ratio of 10:10:80 and mixing it using a bead mill mixer for about 2 hours.

[0240] A porous coating layer forming slurry prepared for both sides of a prepared porous polyolefin substrate was applied using a bar coater, and dried at 60°C for 10 minutes to obtain a separation membrane having a porous coating layer with a thickness of 3 μm on each side of the porous polyolefin substrate.

[0242] Example 2

[0243] A porous polyolefin substrate according to the manufacturing example was prepared as a separator substrate.

[0244] A porous coating layer was formed according to the CCS manufacturing method as follows. Specifically, styrene-butyl acrylate (Tg 40℃, particle size (D)) was used as the binder polymer in water. 50 ) 500 nm) and as inorganic particles boehmite (AlO(OH), particle size (D 50 A slurry for forming a porous coating layer was prepared by adding 500 nm) in a weight ratio of 5:95 and mixing it using a bead mill mixer for about 2 hours.

[0245] A porous coating layer forming slurry prepared for both sides of a prepared porous polyolefin substrate was applied using a bar coater, and dried at 60°C for 10 minutes to obtain a separator with a porous coating layer having a thickness of 2 μm on each side of the porous polyolefin substrate.

[0247] Comparative Example 1

[0248] A porous polyolefin substrate according to a comparative manufacturing example was prepared as a separator substrate.

[0249] As an inorganic particle, alumina (Al2O3, particle size (D 50 In addition to using 500 nm), a separation membrane was obtained in which a porous coating layer with a thickness of 3 μm was provided on each side of a porous polyolefin substrate according to the same method as in Example 1.

[0251] Comparative Example 2

[0252] A porous polyolefin substrate according to a comparative manufacturing example was prepared as a separator substrate.

[0253] As an inorganic particle, alumina (Al2O3, particle size (D 50In addition to using 500 nm), a separation membrane was obtained in which a porous coating layer with a thickness of 2 μm was provided on each side of a porous polyolefin substrate according to the same method as in Example 2.

[0255] Comparative Example 3

[0256] A porous polyolefin substrate according to the manufacturing example was prepared as a separator substrate.

[0257] As an inorganic particle, alumina (Al2O3, particle size (D 50 In addition to using 500 nm), a separation membrane was obtained in which a porous coating layer with a thickness of 2 μm was provided on each side of a porous polyolefin substrate according to the same method as in Example 2.

[0259] Comparative Example 4

[0260] A porous polyolefin substrate according to the manufacturing example was prepared as a separator substrate.

[0261] Aluminum hydroxide (Al(OH)3) as an inorganic particle, particle size (D 50 In addition to using 500 nm), a separation membrane was obtained in which a porous coating layer with a thickness of 2 μm was provided on each side of a porous polyolefin substrate according to the same method as in Example 2.

[0263] [Evaluation of Membrane Properties]

[0264] The physical properties of the membrane were evaluated according to the following method, and the results are shown in Table 2.

[0265] Adhesion strength evaluation

[0266] To evaluate the adhesion between the porous polyolefin substrate and the porous coating layer, peel strength was measured according to the following method.

[0267] First, the separator to be measured was cut to a size of 15 mm X 100 mm. Double-sided adhesive tape was attached to a glass plate, and the surface of the porous coating layer of the prepared separator was attached to the adhesive tape. Afterward, the end of the attached separator was mounted on a UTM device (LLOYD Instrument LF Plus), and a force was applied at 180° at a measurement speed of 300 mm / min to measure the force required to peel off the porous coating layer and the porous polymer substrate.

[0269] airway

[0270] Air permeability was measured by the Gurley method ASTM D726-94. The Gurley used here, representing the resistance to airflow, was measured using a Gurley densometer. The air permeability value was calculated as follows: 1 in⁻¹ of the membrane under measurement, with 100 cc of air flowing under a pressure of 12.2 inH₂O. 2 It was expressed as the time (in seconds) taken to pass through the cross-section, i.e., the air passage time.

[0272] Thermal shrinkage rate

[0273] The separator to be measured was cut to a size of 50mm * 50mm, placed between A4 sheets of paper, and heat-treated in a convection oven at 120℃ for 1 hour, after which the thermal shrinkage rate in the machine direction (MD) and transverse direction (TD) was measured.

[0274] At this time, the thermal shrinkage rate was calculated as [(initial length - length after heat treatment) / (initial length) X 100].

[0275] division Example 1 Example 2 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 porous polyolefin substrate Preparation Example Preparation Example Comparative Manufacturing Example Comparative Manufacturing Example Preparation Example Preparation Example Method for forming a porous coating layer W-SRS CCS W-SRS CCS CCS CCS Total thickness of the membrane (㎛) 15 13 15 13 13 13 Adhesion (gf / 15 mm) 85 80 40 35 40 45 Air permeability (sec / 100 cc) 90 80 90 80 80 82 Thermal shrinkage rate (%, MD / TD) 3 / 3 2 / 1 5 / 5 4 / 3 3 / 3 45 / 42

[0276] As can be seen in Table 2 above, the separator membranes of Example 1 and Example 2 according to one embodiment of the present invention showed excellent adhesion between the porous polyolefin substrate and the porous coating layer, whereas the separator membranes according to Comparative Examples 1 to 4 showed inferior adhesion between the porous polyolefin substrate and the porous coating layer.

[0277] In particular, it was confirmed that when using a porous polyolefin substrate containing a cross-linked polyolefin resin containing silicon-containing organic groups grafted to the polyolefin chain according to the manufacturing example and chromium, the porous coating layer can significantly increase the adhesion between the porous polyolefin substrate and the porous coating layer without being significantly limited by the method of forming the porous coating layer when the porous coating layer contains boehmite (AlO(OH)) as an inorganic particle. More specifically, in the case of Comparative Example 3 using alumina as an inorganic particle, it was confirmed that the adhesion between the porous polyolefin substrate and the porous coating layer was significantly inferior, and in the case of Comparative Example 4 using aluminum hydroxide as an inorganic particle, it was confirmed that not only was the adhesion inferior, but the heat resistance was also significantly inferior due to the low density of aluminum hydroxide.

[0278] Although the present invention has been described above with reference to the embodiments and drawings, those skilled in the art will be able to make various applications and modifications within the scope of the present invention based on the above content.

Claims

Claim 1 A separator for an electrochemical device comprising a porous polyolefin substrate and a porous coating layer formed on at least one surface of the porous polyolefin substrate, wherein the porous polyolefin substrate comprises a cross-linked polyolefin resin, the cross-linked polyolefin resin comprises silicon-containing organic groups grafted to polyolefin chains, the gel fraction is 3% to 80%, and the standard deviation (△d) of the thickness measured at any 100 points is 0.5 μm or less, the porous coating layer comprises inorganic particles and a binder polymer, the inorganic particles comprise boehmite (AlO(OH)), the adhesion strength between the porous polyolefin substrate and the porous coating layer is 70 to 100 gf / 15 mm, and the porous polyolefin substrate further comprises chromium (Cr). Claim 2 delete Claim 3 delete Claim 4 A separator for an electrochemical device according to claim 1, characterized in that the adhesion strength between the porous polyolefin substrate and the porous coating layer is 70 to 95 gf / 15 mm. Claim 5 A separator for an electrochemical device according to claim 1, characterized in that the content of the boehmite is 80 weight% or more based on the total weight of the inorganic particles. Claim 6 A separator for an electrochemical device according to claim 1, wherein the silicon-containing organic group is a residue derived from a vinyl group-containing silane compound, and the vinyl group-containing silane compound comprises vinyltrimethoxysilane, vinyltriethoxysilane, vinyltriacetoxysilane, (3-methacryloxypropyl)trimethoxysilane, (3-methacryloxypropyl)triethoxysilane, vinylmethyldimethoxysilane, vinyl-tris(2-methoxyethoxy)silane, vinylmethyldiethoxysilane, or a mixture of two or more of these. Claim 7 delete Claim 8 A separator for an electrochemical device according to claim 1, characterized in that the chromium content is 0.1 to 20 ppm. Claim 9 A separator for an electrochemical device according to claim 1, characterized in that the crosslinked structure within the crosslinked polyolefin resin comprises a structure derived from the result of a radical polymerization reaction between vinyl groups mediated by a thermal initiator. Claim 10 A separator for an electrochemical device according to claim 9, characterized in that the thermal initiator comprises a peroxide-based compound, a persulfate-based compound, an azo-based compound, or a mixture thereof. Claim 11 An electrochemical device comprising an anode, a cathode, and a separator interposed between the anode and the cathode, wherein the separator is characterized in that it conforms to any one of claims 1, 4 to 6, and 8 to 10.

Citation Information

Patent Citations

  • Crosslinkd polyolefin separator and manufacturing method thereof

    KR1020210123139A

  • Separator for lithium secondary battery and manufacturing method thereof

    KR1020220002155A

  • A separator coated with inorganic materials and a method for manufacturing the same

    KR1020220083881A